A negative electrode material preparation method, a negative electrode material, a negative electrode sheet, and a lithium battery

CN121292534BActive Publication Date: 2026-10-16TIANFU JIANGXI LAB
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511403917.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-28
Publication Date
2026-10-16
Estimated Expiration
2045-09-28

AI Technical Summary

Technical Problem

这种体积变化的反复发生,极易引发电极材料的粉化、脱落或与集流体之间的接触失效,进而造成容量的迅速衰减和循环性能的下降,严重制约了电池的实际使用寿命

Benefits of technology

1、本发明的负极材料制备方法,包括以下步骤:将锂盐和至少五种金属盐混合形成浓度为0.1~1mol/L的盐溶液;向盐溶液加入磷酸盐搅拌30~50min,随后加入络合剂继续搅拌,得到混合溶液;磷酸盐包括磷酸二氢铵、聚磷酸铵、磷酸二氢钾中的一种或几种;在20~80℃的环境下继续搅拌混合溶液直至形成凝胶;烘干、研磨、煅烧、研磨凝胶得到负极材料。本发明采用的至少五种金属盐形成的HEO材料为尖晶石结构,而制备到的PHEO材料不仅保留了HEO材料的尖晶石结构骨架,还通过引入稳定磷酸盐基团,进一步提高了尖晶石结构的稳定性,同时还可以调节各金属盐中的金属价态及提高氧空位浓度,实现更小的颗粒尺寸、更优的材料分散性和更优的导电性等,进而使PHEO材料的锂存储过程主要由零应变特征的表面赝电容主导,从而实现更快的动力学响应和更高的可逆性,极大地降低了负极材料在锂离子嵌入和脱出过程中发生体积膨胀与收缩,将其用于锂电池负极材料可极大地提高锂电池的使用寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121292534B_ABST
    Figure CN121292534B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of batteries, in particular to a negative electrode material preparation method, a negative electrode material, a negative electrode sheet and a lithium battery. The negative electrode material preparation method provided by the application comprises the following steps: mixing lithium salt and at least five kinds of metal salt to form a salt solution with a concentration of 0.1-1 mol / L; adding phosphate into the salt solution and stirring for 30-50 min, then adding a complexing agent to continue stirring, so as to obtain a mixed solution; continuing to stir the mixed solution under the condition of 20-80 DEG C until a gel is formed; and drying, grinding, calcining and grinding the gel to obtain the negative electrode material. The lithium storage process of the prepared negative electrode material is mainly dominated by the surface pseudo-capacitance of zero strain characteristics, so that faster kinetic response and higher reversibility are realized, the volume expansion and shrinkage of the negative electrode material in the lithium ion embedding and disembedding process are greatly reduced, and the service life of the lithium battery can be greatly improved when the negative electrode material is used as the negative electrode material of the lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and in particular to a method for preparing a negative electrode material, the negative electrode material, the negative electrode sheet, and a lithium battery. Background Technology

[0002] In the anode material system of lithium-ion batteries, metal oxide materials based on conversion reaction mechanisms have attracted widespread attention from researchers in recent years, mainly due to their higher theoretical specific capacity, which is significantly better than that of currently widely used graphite-based anode materials. These materials exhibit enormous application potential and can better meet the growing demand for high-energy-density lithium-ion batteries in fields such as new energy vehicles, portable electronic devices, and large-scale energy storage. Therefore, they are considered an important development direction for next-generation high-performance anode materials.

[0003] However, these materials also face certain technical challenges. During battery cycling, the repeated insertion and extraction of lithium ions cause significant phase structure transformations in the material, accompanied by substantial structural stress accumulation, leading to significant volume expansion and contraction of the active material. This repeated volume change can easily cause pulverization, detachment, or contact failure between the electrode material and the current collector, resulting in rapid capacity decay and reduced cycle performance, severely limiting the actual lifespan of the battery. Summary of the Invention

[0004] To reduce the volume expansion and contraction of the negative electrode material during lithium ion insertion and extraction, this invention provides a method for preparing the negative electrode material, the negative electrode material, the negative electrode sheet, and the lithium battery.

[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution: A method for preparing a negative electrode material includes the following steps: A salt solution with a concentration of 0.1–1 mol / L is formed by mixing lithium salt with at least five metal salts. Add phosphate to the salt solution and stir for 30-50 minutes, then add a complexing agent and continue stirring to obtain a mixed solution; the phosphate includes one or more of ammonium dihydrogen phosphate, ammonium polyphosphate, and potassium dihydrogen phosphate; Continue stirring the mixture at 20–80°C until a gel forms; and The anode material is obtained by drying, grinding, calcining, and grinding the gel.

[0006] Preferably, the metal salt includes at least five of the following: chromium salt, manganese salt, iron salt, cobalt salt, nickel salt, zinc salt, copper salt, and magnesium salt; the lithium salt is LiNO3; and the metal salt is a metal nitrate; the complexing agent includes one or a combination of several of the following: anhydrous citric acid, tartaric acid, ethylenediaminetetraacetic acid, and oxalic acid.

[0007] Preferably, the nominal phosphorus doping concentration in the negative electrode material is 1% to 30%.

[0008] Preferably, the specific steps for obtaining the negative electrode material by drying, calcining, and grinding the gel include: The gel is dried at 100–150°C until it is completely dry, and then ground into powder. The ground powder is calcined at 600-800℃ for 1-3 hours to obtain calcined powder; The negative electrode material is obtained by grinding the calcined powder.

[0009] To solve the above-mentioned technical problems, the present invention provides another technical solution as follows: A negative electrode material is prepared by the above-described negative electrode material preparation method. The negative electrode material includes a PO bond of phosphate and a POM bond formed by the coordination bond between phosphate and the metal ion of the metal salt, where M represents the metal ion.

[0010] Preferably, the chemical formula of the negative electrode material is [P x (LiCrMnFeCoZn) 1-x ]3O4, of which, .

[0011] Preferably, the negative electrode material is in particulate form with a particle size of 50–200 nm.

[0012] Preferably, when the nominal phosphorus doping concentration of the negative electrode material is 20%, the lattice parameters a=b=c=8.247279Å and V=560.96Å are obtained. 3 .

[0013] To solve the above-mentioned technical problems, the present invention provides another technical solution as follows: A negative electrode sheet includes a current collector and the aforementioned negative electrode material disposed on at least one surface of the current collector.

[0014] To solve the above-mentioned technical problems, the present invention provides another technical solution as follows: A lithium battery, characterized in that: it includes the above-mentioned negative electrode, electrolyte, positive electrode, separator, and a shell for accommodating the negative electrode, electrolyte, positive electrode and separator, wherein the separator is located between the negative electrode and the positive electrode, and the electrolyte is filled in the shell.

[0015] Compared with the prior art, the negative electrode material preparation method, negative electrode material, negative electrode sheet and lithium battery provided by the present invention have the following beneficial effects: 1. The method for preparing the negative electrode material of the present invention includes the following steps: mixing lithium salt and at least five metal salts to form a salt solution with a concentration of 0.1 to 1 mol / L; adding phosphate to the salt solution and stirring for 30 to 50 minutes, followed by adding a complexing agent and continuing to stir to obtain a mixed solution; the phosphate includes one or more of ammonium dihydrogen phosphate, ammonium polyphosphate, and potassium dihydrogen phosphate; continuing to stir the mixed solution at an environment of 20 to 80°C until a gel is formed; drying, grinding, calcining, and grinding the gel to obtain the negative electrode material. The HEO material formed by at least five metal salts used in this invention has a spinel structure. The prepared PHEO material not only retains the spinel structure framework of the HEO material, but also further improves the stability of the spinel structure by introducing stable phosphate groups. At the same time, it can also adjust the metal valence state in each metal salt and increase the oxygen vacancy concentration to achieve smaller particle size, better material dispersion and better conductivity. As a result, the lithium storage process of the PHEO material is mainly dominated by the surface pseudocapacitance with zero strain characteristics, thereby achieving faster kinetic response and higher reversibility. This greatly reduces the volume expansion and contraction of the anode material during lithium ion insertion and extraction. Using it as a lithium battery anode material can greatly improve the service life of lithium batteries.

[0016] 2. The metal salts of this invention include at least five of the following: chromium salts, manganese salts, iron salts, cobalt salts, nickel salts, zinc salts, copper salts, and magnesium salts. Most of the elements selected in this invention are in the same period and have similar ionic radii, making it easier to achieve mutual coordination.

[0017] 3. The nominal phosphorus doping concentration in the negative electrode material of the present invention is 1% to 30%. By doping with an appropriate concentration of phosphorus, the active sites can be further improved, thereby increasing the specific capacity.

[0018] 4. The specific steps of the present invention for obtaining the negative electrode material by drying, calcining, and grinding the gel include: drying the gel at 100-150°C to ensure complete drying, and then grinding it into powder; calcining the ground powder at 600-800°C for 1-3 hours to obtain calcined powder; and grinding the calcined powder to obtain the negative electrode material. By performing multiple grinding processes—grinding, calcining, and then grinding again—the size of the PHEO material can be further refined, the surface area increased, and more active sites can be provided for lithium ions, thereby improving the specific capacity.

[0019] 5. The negative electrode material of the present invention is prepared by the above-described negative electrode material preparation method. The negative electrode material includes PO bonds of phosphate ions and POM bonds formed by the coordination bonding of phosphate ions and metal ions of metal salts, where M represents metal ions. The formation of these bonds can make the crystal structure more compact and stabilize the framework structure of the material, thereby inhibiting the destruction of the spinel structure and enabling the PHEO material to have zero-strain material properties during the lithium ion extraction and insertion process.

[0020] 6. The negative electrode material of the present invention is granular with a particle size of 50-200 nm. Through P doping, the P element may act as a nucleating agent during the synthesis process, increasing the nucleation sites and resulting in the formation of smaller and more uniform grains.

[0021] 7. The negative electrode sheet of the present invention includes a current collector and the aforementioned negative electrode material disposed on at least one surface of the current collector. It has the same beneficial effects as the aforementioned negative electrode material, and will not be elaborated upon here.

[0022] 8. The lithium battery of the present invention includes the above-described negative electrode, electrolyte, positive electrode, separator, and a housing containing the negative electrode, electrolyte, positive electrode, and separator. The separator is located between the negative electrode and the positive electrode, and the electrolyte is filled within the housing. It has the same beneficial effects as the negative electrode described above, and will not be elaborated further here. Attached Figure Description

[0023] To more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0024] Figure 1 This is the Raman spectrum of the PHEO material prepared by the negative electrode material preparation method provided in the first embodiment of the present invention.

[0025] Figure 2 The images shown are high-angle annular dark-field image-scanning transmission electron microscope (HAADF-STEM) images and elemental distribution (Energy-Dispersive X-ray Spectroscopy, EDS) diagrams of PHEO materials prepared by the negative electrode material preparation method provided in the first embodiment of the present invention.

[0026] Figure 3 This is an inductively coupled plasma optical emission spectrometry (ICP-OES) spectrum of the PHEO material prepared by the negative electrode material preparation method provided in the first embodiment of the present invention.

[0027] Figure 4 The image shows the wide-angle X-ray diffraction (XRD) pattern and (311) peak shift of PHEO materials with different nominal P doping concentrations prepared by the negative electrode material preparation method provided in the first embodiment of the present invention.

[0028] Figure 5 yes Figure 4 A schematic diagram of the results of fine-tuning with PHEO-20%.

[0029] Figure 6 This is a high-resolution X-ray photoelectron spectroscopy (XPS) image of the PHEO material provided in the second embodiment of the present invention.

[0030] Figure 7 This is a schematic diagram of the differential scanning calorimetry (DSC) test results of PHEO and HEO materials provided in the second embodiment of the present invention.

[0031] Figure 8 This is a schematic diagram showing the valence percentages of different elements in the PHEO material and HEO material provided in the second embodiment of the present invention.

[0032] Figure 9 This is a high-resolution O1s spectrum of the PHEO material and HEO material provided in the second embodiment of the present invention.

[0033] Figure 10 The second embodiment of the present invention provides the electron paramagnetic resonance (EPR) spectra of PHEO and HEO materials.

[0034] Figure 11 This is a schematic diagram of the density functional theory (DFT) calculation results of the PHEO material provided in the second embodiment of the present invention.

[0035] Figure 12 The PHEO material provided in the second embodiment of the present invention is at 0.1 mVs -1 The first three cyclic voltammetry curves.

[0036] Figure 13 The PHEO material provided in the second embodiment of the present invention is used at different scanning rates (0.1-1.0 mVs). -1 Cyclic voltammetry curves under ( ).

[0037] Figure 14 The PHEO material provided in the second embodiment of the present invention is used at different scanning rates (0.1-1.0 mVs). -1 A schematic diagram of the capacitance contribution ratio analysis under ( ).

[0038] Figure 15 a is a transmission electron microscope image of the PHEO material provided in the second embodiment of the present invention.

[0039] Figure 15 b is a schematic diagram of the morphological changes of the PHEO material after the first cycle provided in the second embodiment of the present invention.

[0040] Figure 15 c is a scanning dark-field electron microscope image of the PHEO material after cycling, provided in the second embodiment of the present invention.

[0041] Figure 16 This is the in-situ XRD pattern of PHEO material during the first charge-discharge cycle of the PHEO material provided in the second embodiment of the present invention, which shows the phase transition process in real time.

[0042] Figure 17 The PHEO material provided in the second embodiment of the present invention has a voltage range of 0.01-3V and a viscosity of 0.2 A·g. -1 The first three Galvanostatic Charge-Discharge (GCD) curves at current density.

[0043] Figure 18 The PHEO material provided in the second embodiment of the present invention is at 0.5 A·g -1 Schematic diagram of cyclic performance and corresponding Coulomb effect under the given conditions.

[0044] Figure 19 The PHEO material provided in the second embodiment of the present invention is at 2 A·g -1 Schematic diagram of cyclic performance and corresponding Coulomb effect under the given conditions.

[0045] Figure 20 This is a three-dimensional in-situ electrochemical impedance spectroscopy (EIS) distribution diagram of the PHEO material provided in the second embodiment of the present invention during the first constant current cycling process.

[0046] Figure 21 This is the dynamic impedance time (DRT) curve of the PHEO material provided in the second embodiment of the present invention, calculated based on EIS data. Detailed Implementation

[0047] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0048] In the embodiments provided by this invention, it should be understood that "B corresponding to A" means that B is associated with A, and B can be determined based on A. However, it should also be understood that determining B based on A does not mean determining B solely based on A; B can also be determined based on A and / or other information.

[0049] It should be understood that the phrase "one embodiment" or "an embodiment" throughout the specification means that a specific feature, structure, or characteristic related to the embodiment is included in at least one embodiment of the invention. Therefore, "in one embodiment" or "in an embodiment" appearing throughout the specification does not necessarily refer to the same embodiment. Furthermore, these specific features, structures, or characteristics can be combined in any suitable manner in one or more embodiments. Those skilled in the art should also recognize that the embodiments described in the specification are optional embodiments, and the actions and modules involved are not necessarily essential to the invention.

[0050] In various embodiments of the present invention, it should be understood that the sequence number of each process does not necessarily imply the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.

[0051] The flowcharts and block diagrams in the accompanying drawings illustrate methods and possible architectures, functions, and operations according to various embodiments of this application. In this regard, each block in the flowchart or block diagram may represent part of a step. It should also be noted that in some alternative implementations, the functions indicated in the blocks may occur in a different order than those indicated in the drawings. For example, two consecutively indicated blocks may actually be executed substantially in parallel, or they may sometimes be executed in reverse order, depending on the functions involved.

[0052] The first embodiment of the present invention provides a method for preparing a negative electrode material, comprising the following steps: S1. Mix lithium salt with at least five metal salts to form a salt solution with a concentration of 0.1 to 1 mol / L; S2. Add phosphate to the salt solution and stir for 30-50 minutes, then add a complexing agent and continue stirring to obtain a mixed solution; the phosphate includes one or more of ammonium dihydrogen phosphate, ammonium polyphosphate, and potassium dihydrogen phosphate; S3. Continue stirring the mixed solution at 20–80°C until a gel forms; and S4. Drying, grinding, calcining, and grinding the gel to obtain the negative electrode material.

[0053] It should be noted that, since the negative electrode material prepared by the negative electrode material preparation method provided in the first embodiment of the present invention includes the introduction of high-entropy oxide (HEO) material formed by at least five metal salts and phosphate material, for ease of understanding and description, the negative electrode material prepared by the negative electrode material provided in the first embodiment of the present invention is abbreviated as PHEO material (phosphorus-doped high-entropy oxide negative electrode material) in the specification. PHEO and P-HEO in the accompanying drawings of the embodiments of the present invention have the same meaning and are both PHEO materials.

[0054] It is understood that the negative electrode material provided in the first embodiment of the present invention contains a high-entropy oxide material, and the high configurational entropy (S) of this type of material config ≥1.5R exhibits a significant entropy stabilization effect, effectively mitigating volume changes caused by phase transitions and strain during relithiation or delithiation. This reduces volume expansion and contraction of the anode material during lithium-ion insertion and extraction, thereby significantly improving capacity retention and extending service life. Simultaneously, the addition of phosphate, where phosphorus combines with oxygen to form highly stable phosphate tetrahedral structural units, further enhances the material's structural stability, further reducing volume expansion and contraction during lithium-ion insertion and extraction. Relithiation refers to the process of lithium ions re-inserting or returning to the electrode material's crystal lattice; delithiation refers to the process of lithium ions being extracted from the electrode material's crystal lattice.

[0055] Furthermore, the HEO material formed by at least five metal salts used in this invention has a spinel structure. The prepared PHEO material not only retains the spinel structure framework of the HEO material, but also further improves the stability of the spinel structure by introducing stable phosphate groups. At the same time, it can also adjust the metal valence state in each metal salt and increase the oxygen vacancy concentration to achieve smaller particle size, better material dispersion and better conductivity. As a result, the lithium storage process of the PHEO material is mainly dominated by the surface pseudocapacitance with zero strain characteristics, thereby achieving faster kinetic response and higher reversibility. This greatly reduces the volume expansion and contraction of the anode material during lithium ion insertion and extraction. Using it as a lithium battery anode material can greatly improve the service life of lithium batteries.

[0056] It is understood that zero-strain characteristic refers to a very small change in unit cell volume (<1%) during cycling. In the embodiments of this invention, surface pseudocapacitance refers to Li... +This is a mechanism for lithium storage via rapid, reversible redox reactions on and near the surface of PHEO materials. It can be understood that in this surface pseudocapacitive-dominated lithium storage mode, the chemical reaction is limited to atoms on or near the surface of the PHEO material. It does not rely on the slow solid-state diffusion of lithium ions into the bulk phase; instead, lithium ions are stored through adsorption, desorption, or rapid epitaxial insertion (without causing lattice distortion). During lithium ion insertion and extraction, there is almost no expansion or contraction of the PHEO material's volume. Furthermore, because there is no slow bulk diffusion limitation, its charge and discharge rates are extremely fast, exhibiting excellent rate performance. This reaction is highly reversible and causes almost no damage to the material structure, resulting in a very long cycle life.

[0057] It is understood that this invention incorporates phosphorus into high-entropy oxide materials by adding phosphate. Non-metallic phosphorus (P) is located at the boundary between metals and non-metals in the periodic table, exhibiting high electronegativity and metal-like properties, which significantly enhance the electronic conductivity of the material. Furthermore, phosphorus differs significantly from metals in electronegativity and ionic radius, allowing electrons to rapidly transfer from metals to phosphorus doping sites. This promotes the formation of electron-rich and electron-deficient local structures during lithium-ion insertion and extraction, thereby significantly improving electrochemical reactivity. More importantly, phosphorus combines with oxygen to form highly stable phosphate (PO4). 3- The tetrahedral structural unit greatly enhances the structural integrity and cycle life of the material.

[0058] Furthermore, the metal salt includes at least five of the following: chromium salt, manganese salt, iron salt, cobalt salt, nickel salt, zinc salt, copper salt, and magnesium salt. Specifically, the lithium salt is LiNO3, and the metal salt is a metal nitrate.

[0059] As a preferred option, the metal salts include five types: chromium salts, manganese salts, iron salts, cobalt salts, and zinc salts. Specifically, they are Cr(NO3)3·9H2O, Mn(NO3)2·6H2O, Fe(NO3)3·9H2O, Co(NO3)2·6H2O, and Zn(NO3)2.

[0060] Furthermore, combined Figure 1 Raman spectroscopy analysis revealed that the PHEO material has a spinel structure, and its characteristic peak is located at 478.3 cm⁻¹. -1 557.3 cm -1 654.3 cm -1 The frequency and intensity of these characteristic peaks are closely related to the distribution of cations in octahedral and tetrahedral sites and the symmetry of the crystal structure.

[0061] As a preferred embodiment, after step S1, the salt solution is stirred for 30–60 minutes before proceeding to step S2, which can make the lithium salt and at least five metal salts more uniformly mixed. This can be done by magnetic stirring, and the specific stirring time can also be 30–40 minutes, 40–50 minutes, 50–60 minutes, etc.

[0062] Specifically, the concentration of the salt solution in step S1 can also be 0.1–0.5 mol / L, 0.5–0.8 mol / L, 0.8–1 mol / L, etc. This invention mixes lithium salt with at least five metal salts to form a salt solution with a concentration below 1 mol / L. The lower concentration of the salt solution allows for a more uniform mixing of the lithium salt and at least five metal salts. Simultaneously, the addition of a complexing agent and stirring also forms a uniform mixed solution, further achieving uniform dispersion of the elements. The complexing agent used in step S2 includes one or more of anhydrous citric acid, tartaric acid, ethylenediaminetetraacetic acid, oxalic acid, etc. Magnetic stirring is used, and the stirring time can be 30–40 min, 40–50 min, etc., further achieving uniform dispersion of the elements in the solution through stirring. The temperature range in step S3 can also be 20–30℃, 30–40℃, 40–50℃, 50–60℃, 60–70℃, 70–80℃, etc.

[0063] It is understandable that the uniform dispersion of elements in HEO materials allows for thermodynamic stability through the high-entropy effect, enhanced mechanical properties and slowed diffusion through the lattice distortion effect, and ultimately, through the slow diffusion effect and the "cocktail" effect, it exhibits comprehensive performance surpassing that of traditional materials in multiple dimensions such as mechanics, chemistry, and physics. The "cocktail" effect refers to the synergistic effect between elements that produces comprehensive properties that no single element possesses.

[0064] Figure 2 This is a high-resolution elemental distribution map of the prepared 50nm PHEO material, combined with... Figure 2 It is evident that the distribution of Cr, Mn, Fe, Co, Zn, P, and O elements within the PHEO material grains is highly uniform. Combined with... Figure 3 Inductively coupled plasma optical emission spectroscopy (ICP-OES) analysis showed that the content of metal elements and phosphorus in the PHEO material was within the atomic percentage range of 5% to 35%, which meets the high-entropy oxide standard and supports the entropy stabilization effect. These results confirm the successful synthesis of phase-pure and homogeneous phosphorus-doped high-entropy materials, in which phosphorus doping achieves particle size reduction and lattice distortion control without affecting the integrity of the spinel structure.

[0065] Furthermore, the specific steps of step S4 include: S41. Dry the gel at 100-150℃ until it is completely dry, then grind it into powder. S42. The ground powder is calcined at 600–800℃ for 1–3 hours to obtain calcined powder; and S43. Grind and calcinate the powder to obtain the negative electrode material.

[0066] Specifically, the temperature range in step S41 can also be 100–110℃, 110–120℃, 120–130℃, 130–140℃, 140–150℃, etc. The temperature range in step S42 can also be 600–650℃, 650–700℃, 700–750℃, 750–800℃, etc., and the calcination time can also be 1–1.5h, 1.5–2h, 2–2.5h, 2.5–3h, etc.

[0067] It is understood that in step S4 of the present invention, by grinding, calcining and grinding again, multiple grinding processes can further refine the size of the PHEO material and increase its surface area, which can provide more active sites for lithium ions and thus improve the specific capacity.

[0068] Further, the molar ratio of lithium salt:chromium salt:manganese salt:iron salt:cobalt salt:zinc salt:complexing agent:phosphate is 1:1:1:1:1:1:(0.1-0.6):6. Specifically, it can be 1:1:1:1:1:1:0.1:6, 1:1:1:1:1:1:0.2:6, 1:1:1:1:1:1:0.3:6, etc., corresponding to nominal phosphorus doping concentrations of 10%, 20%, and 30%, respectively, preferably 1:1:1:1:1:1:1:0.2:6. The nominal phosphorus doping concentration in the PHEO material is 1% to 30%. It can be understood that the phosphorus doping concentration mentioned in the embodiments of this invention is the nominal doping concentration, which refers to the theoretical concentration of the dopant element calculated at the initial feeding stage during the material preparation process.

[0069] Combination Figure 4As can be seen, XRD patterns confirm that all PHEO materials possess a pure spinel phase structure (JCPDS# 80-1668), with no impurities detected. In the figure, PHEO-0%, PHEO-10%, PHEO-20%, and PHEO-30% represent nominal P doping concentrations of 0%, 10%, 20%, and 30%, respectively. The high-resolution (311) peak shows that the PHEO material with a 20% P doping concentration exhibits a significant upward shift, indicating successful phosphorus doping leading to lattice contraction. With increasing doping concentration, the shift amplitude first increases and then decreases. This is because phosphorus atoms initially occupy larger transition metal sites, and their smaller atomic radius induces lattice contraction. When the doping concentration exceeds 30%, phosphorus atoms gradually occupy smaller lithium-ion sites, resulting in a lattice size change of first contraction and then expansion. Therefore, high-concentration P doping exceeding 30% leads to phosphorus atoms occupying lithium-ion sites, causing increased lattice distortion and potentially disrupting the stability of the spinel structure, thus adversely affecting electrochemical performance. Therefore, a 20% P doping concentration was determined to be the optimal value. Therefore, in the illustrations of the embodiments of the present invention, all illustrations that do not mention the nominal phosphorus doping concentration value represent a nominal phosphorus doping concentration of 20%.

[0070] Further integration Figure 5 (PHEO-20% sample), the crystal structure parameters of the PHEO material obtained through refinement are shown in Table 1. It can be seen that the broader diffraction peaks of the PHEO material further indicate the lattice distortion and heterogeneous strain induced by phosphorus. Specifically, when the nominal doping concentration of P is 20%, the lattice parameters of the anode material are a=b=c=8.247279Å and V=560.96Å. 3 .

[0071] Table 1: Crystal structure parameters of PHEO materials

[0072] In summary, the anode material preparation method provided in the first embodiment of the present invention can prepare a highly stable material with zero strain characteristics, and also has high specific capacity and other characteristics, which can significantly improve the performance of the anode material.

[0073] The second embodiment of the present invention provides a negative electrode material (hereinafter referred to as PHEO material), which is prepared by the negative electrode material preparation method provided in the first embodiment of the present invention. The negative electrode material provided in the second embodiment of the present invention includes PO bonds of phosphate ions and POM bonds formed by the coordination bonding of phosphate ions and metal ions of metal salts, where M represents metal ions.

[0074] Specific combination Figure 6The P2P spectrum of the PHEO material shows two peaks at 132.64 eV and 133.93 eV, corresponding to PO and POM bonds, respectively. The formation of these bonds can make the crystal structure more compact and stabilize the framework structure of the material, thereby inhibiting the destruction of the spinel structure and giving the PHEO material more stable structural characteristics during lithium ion extraction and insertion.

[0075] As a preferred embodiment, the metallic elements in the PHEO material include lithium, as well as chromium, manganese, iron, cobalt, and zinc. Specifically, the chemical formula of the PHEO material is [P x (LiCrMnFeCoZn) 1-x ]3O4, of which, PHEO material is in granular form with a particle size of 50–200 nm, specifically 20–100 nm, 100–150 nm, 150–200 nm, etc.

[0076] To further verify the performance of PHEO materials, a comparative analysis was conducted below using PHEO materials with a nominal phosphorus doping concentration of 20% and undoped HEO materials.

[0077] Combination Figure 7 Differential scanning calorimetry (DSC) results showed that PHEO material exhibited a stable exothermic process in the range of room temperature to 800°C, while HEO material initially exothermed and then underwent a mild endothermic transition in the range of 600°C to 800°C. This is consistent with the results of Cr... 3+ Mn 3+ Fe 3+ Co 3+ This is related to the reduction effect of metal cations. The absence of this endothermic effect in PHEO materials further highlights the importance of phosphorus doping for lattice stability; this effect originates from phosphate groups (PO4). 3- The introduction of these groups can enhance the stability of the crystal framework.

[0078] Combination Figure 8 By comparing the metal valence states of PHEO and HEO materials, it can be seen that ( Figure 8 In the diagram, Cr is located on the far left, and O is on the far right. For each metallic element, the left side represents HEO, and the right side represents PHEO. 6+ The content plummeted from 84.68% to 14.28%, Co 3+ The content decreased from 52.12% to 26.68%, indicating that P doping in PHEO materials can adjust the valence ratio of metal ions and increase the number of metal states with free 3d electrons. The increase in the number of metal states with free 3d electrons in PHEO materials can effectively improve electronic conductivity and rate performance.

[0079] Combination Figure 9 High-resolution O1s spectra were decomposed into adsorbed oxygen (O2). A ), oxygen vacancy (O V ) and lattice oxygen (O L 19. O V The content increased from 41.77% in HEO material to 64.01% in PHEO material. Although Li + Doping mainly produces O in HEO materials. V However, in PHEO materials, Li + This phenomenon synergistically enhances vacancy concentration with P doping. Furthermore, in... Figure 10 The results are supported by electron paramagnetic resonance (EPR). Combined with... Figure 10 When g = 2.000, the PHEO material exhibits stronger O V Signal. O V Increasing the concentration is particularly beneficial to electrode materials because it promotes ion adsorption and provides more active sites for surface-mediated charge storage, thereby increasing the specific capacity of PHEO materials.

[0080] Combination Figure 11 Density functional theory (DFT) calculations show that the band gap of PHEO materials shrinks to 0.30 eV, making it easier for electrons to transition from the valence band to the conduction band, thereby improving conductivity. This phenomenon is attributed to the regulatory effect of phosphorus doping on the electronic structure—it not only increases oxygen vacancies (O2- ... V The number of sites also generates more free electrons around the metal sites.

[0081] As can be seen from the above analysis, the PHEO material provided in the second embodiment of the present invention has the characteristics of high stability, high conductivity, high electronic conductivity, and high specific capacity.

[0082] Furthermore, the present invention uses CR2032 button cells to evaluate the performance of PHEO materials with a nominal phosphorus doping concentration of 20%.

[0083] Specifically, the electrode slurry for the CR2032 button cell is prepared by uniformly mixing 70% active material PHEO, 20% conductive graphite, and 10% polyvinylidene fluoride (PVDF) in N-methylpyrrolidone (NMP) solvent. The slurry is coated onto a copper current collector and dried in a vacuum oven at 80°C for 12 hours to obtain the negative electrode. After pressing, the electrode film is cut into circular pieces with a diameter of 12 mm, and the active material mass loading is approximately 1.0 mg / cm². The button cell is assembled in an argon-filled glove box using conventional methods in the art, with water and oxygen content controlled below parts per million. The electrolyte is prepared by dissolving 1.0 mol / L LiPF6 in a mixed solvent of acetonitrile, ethylene glycol, and dimethylformamide (volume ratio 1:1:1). The counter electrode uses lithium metal, and the separator is a Whatman GF / D glass fiber membrane (19 mm in diameter).

[0084] Combination Figure 12 Cyclic voltammetry curves showed that the curves of the third cycle of the PHEO material highly overlapped with those of the second cycle, reflecting the high reversibility, low polarizability, and efficient charge transfer capability of the PHEO material. The PHEO material exhibited unique cyclic voltammetric response characteristics in the first cycle, with its initial reduction peak appearing at 1.40 V, which stemmed from the strong interaction between the PO group and lithium ions. This high-potential characteristic is related to the phosphate group (PO4). 3- This aligns with the chemical pattern that phosphorus (P) tends to be reduced at higher potentials. The second reduction peak at ~0.93 V corresponds to the lithium-ion intercalation process, while an irreversible peak associated with the solid-electrolyte interphase (SEI) is observed at ~0.25 V. In subsequent cycles, the reduction peak potential shifts negatively from 0.93 V to 0.62 V, while the oxidation peak potential shifts downward. These potential changes indicate that phosphorus doping can modulate the chemical structure of the oxide matrix, inducing a lithium-ion storage mechanism dominated by surface pseudocapacitance with zero strain characteristics.

[0085] Combination Figure 13 , Figure 13 Cyclic voltammetry curves of the PHEO material at different scan rates (v) are presented, and these curves can be used to reflect lithium-ion diffusion kinetics. In the reversible system, the peak current (I0) is... p At 25°C, it follows the Landles-Sevcik equation:

[0086] Where n is the number of transferred electrons, and A is the electrode area (cm²). 2 ), D Li+ It is Li + Diffusion coefficient (cm)2 ·s -1 C is Li + Carrier concentration (mol·cm) -3 ), ν scan rate (V·s) -1 ), I p The peak current (A) is obtained by logging (I). p The slope (b value) obtained by fitting ν-log(ν) for PHEO material is 0.72, indicating that PHEO material has a strong pseudocapacitive effect.

[0087] To verify this conclusion, we systematically measured values ​​from 0.1 to 1 mV·s -1 Capacitance contribution analysis was performed at different scan rates, and the results are as follows: Figure 14 As shown, at 0.1 mV·s -1 and 1 mV·s -1 At that time, the pseudocapacitance accounted for 41.8% and 87.5%, respectively. This increase in pseudocapacitance mainly stemmed from: phosphorus doping inducing a decrease in grain size and an increase in specific surface area; and abundant surface defects leading to Li + Adsorption provides more active sites. This enhanced pseudocapacitive effect accelerates the Li... + The insertion / extraction process maintains high rate performance and capacity retention. Overall, these findings suggest that phosphorus doping-induced surface pseudocapacitance plays a crucial role in enhancing fast Li⁺ storage and electrochemical kinetics.

[0088] Combination Figure 15 To elucidate the electrochemical lithium storage mechanism of PHEO materials, transmission electron microscopy (TEM) characterization of the electrodes was performed after the first cycle (a-15c). High-resolution TEM analysis showed that no lithium oxide phase was detected in the PHEO materials. Therefore, PHEO materials exhibit a unique Li... + The storage mechanism, with its excellent reversibility, provides a significant advantage for long-term electrochemical performance.

[0089] Combination Figure 16 To further investigate the lithium storage mechanism of PHEO materials, in-situ XRD analysis was performed during the first cycle. Under open-circuit voltage conditions, the (220), (311), (222), (400), (511), and (440) crystal planes of the PHEO material electrode all showed clearly characteristic diffraction peaks. When discharged to 0.01 V and subsequently charged to 3 V, these diffraction peaks did not show significant intensity changes or disappearance, but the main peak shifted slightly with respect to different charge states. The magnified (311) peak showed that with increasing Li... + The peak shifts to a higher angle upon embedding, then shifts back to a lower angle after charging. This is attributed to the embedded Li. +The strong binding force with anions. This invariance confirms that the PHEO material maintains a zero-strain structural framework throughout lithium storage, demonstrating that the PHEO material has a stable chemical structure, which enables it to exhibit excellent performance during charge-discharge cycles.

[0090] Combination Figure 17 , Figure 17 The study demonstrated that PHEO materials operate at 0.2 A·g in the range of 0.01–3 V. -1 The first three galvanostatic charge-discharge (GCD) curves at current densities show a low potential plateau resulting from irreversible SEI formation. An additional plateau of ~1.4 V appears during the first discharge, consistent with the P-related reduction peak in its cyclic voltammetry curves, verifying its unique P-doped redox characteristics. At 0.5, 1, 2, and 5 A·g -1 At current densities of 417.1, 415.0, 361.7, and 259.0 mAh g⁻¹, respectively. -1 The capacity. When the current recovers to 0.5 A·g -1 At that time, the capacity of the PHEO material rapidly recovered to 471.4 mAh g. -1 And after 300 cycles, it gradually climbs to ~800 mAh g -1 .

[0091] Combination Figure 18 At 0.5 A·g -1 Under the given conditions, the initial capacity of the PHEO material was 686.2 mAh g. -1 Its significant activation effect enabled it to reach a capacity of 798.8 mAh g after 200 cycles. -1 (Capacity retention rate 116.4%), and in terms of first-cycle coulombic efficiency, PHEO material performed at 73.0%.

[0092] Combination Figure 19 , in 2 A·g -1 Under current, the PHEO material achieved a capacity of 817.2 mAh g after 1000 cycles. -1 (Capacity retention of 149.6%). This sustained capacity improvement stems from the cycle-induced grain refinement effect—a process that expands the material's surface area and exposes more active sites, resulting in a higher specific capacity. Therefore, the phosphorus element in high-entropy graphene oxide not only comprehensively enhances electrochemical performance but also significantly extends cycle life.

[0093] Combination Figure 20 Three-dimensional in-situ EIS spectra were used to analyze the impedance changes during the charging and discharging process of Li. + Evolution of diffusion kinetics. In the initial discharge phase (2.4–0.9 V), Rct Both charge transfer resistance and diffusion impedance are high; PHEO materials maintain stable impedance due to their richer diffusion channels. With increasing depth of discharge (0.9-0.01V), R... ct The capacity continues to decrease, consistent with the sharp discharge peak during the first cycle. The irreversible capacity loss primarily originates from SEI-related Li. + Consumption. When charged to 1.2V, the impedance decreases further, due to the reaction of the metal with lithium oxide and the recombination of the surface-active material into Li. x MO y This is due to the intermediate. Only above 2.4 V does Li... x MO y Delithiation will occur only when PHEO materials maintain low diffusion resistance, indicating that PHEO materials have a high ion diffusion rate.

[0094] Combination Figure 21 The Distribution of Relaxation Times (DRT) analysis technique was used to analyze impedance variations. Unlike traditional equivalent circuit modeling methods, DRT does not require a pre-defined equivalent circuit model. This method effectively reduces the reliance on prior assumptions in electrochemical system research, avoiding potential biases and errors caused by inappropriate assumptions. This method can identify three main relaxation time intervals: the ohmic resistance region (R... s 10 -5 -10 -4 s), SEI-related resistance region (R) SEI 10 -4 -10 -1 s) and charge transfer resistance region (R ct 10 -1 -10 0 s). Where R SEI With R ct The most significant differences were observed in the changes observed in the electrolyte, indicating that phosphorus doping stabilizes the SEI structure, thereby mitigating electrode breakage / remodeling caused by volume changes and maintaining the stability of the electrode-electrolyte interface. This structural stability, coupled with improved electronic conductivity, underpins the superior ion and electron transport properties of PHEO materials.

[0095] In summary, the excellent electrochemical activity and cycling stability exhibited by PHEO materials obtained through phosphorus doping stem from the combined advantages of their structural structure and electronic properties. The high electronegativity of phosphorus significantly increases the number of lithium active sites, thus providing a favorable environment for lithium production. + The insertion and extraction of oxygen provide more accessible pathways. Simultaneously, the large number of oxygen vacancies (O2) generated during the doping process... VThe high concentration of phosphorus (P) provides abundant and rapid transport channels for lithium ions, significantly improving ion diffusion efficiency. The lattice distortion induced by phosphorus (P) modulates the intrinsic electronic properties of the spinel structure, thereby enhancing its lithium storage capacity. These advantages are further strengthened by the synergistic stabilizing effect of pre-lithiation treatment, the formation of strong covalent PO bonds, and the inherent entropy stabilization effect of the high-entropy system. In summary, these characteristics collectively ensure the stability of the material structure and enable it to maintain excellent electrochemical performance during long-term cycling. The PHEO material exhibits high capacity, excellent rate performance, and outstanding cycling stability at 0.5 A·g⁻¹. -1 The current reached 686.2 mAh g. -1 And in 2 A·g -1 After 1000 cycles under current, it still retains 149.6% of its initial capacity. Mechanistic analysis shows that the lithium storage process of PHEO material is mainly dominated by surface pseudocapacitance with zero strain characteristics, thereby achieving faster kinetic response and higher reversibility. These results indicate that PHEO material is an ideal candidate anode material for high-performance lithium-ion batteries. It is understood that the anode material provided in the second embodiment of the present invention has the same beneficial effects as the anode material preparation method provided in the first embodiment of the present invention, and will not be repeated here.

[0096] A third embodiment of the present invention provides a negative electrode sheet, comprising a current collector and a negative electrode material provided in the second embodiment of the present invention disposed on at least one surface of the current collector. It is understood that the negative electrode sheet provided in the third embodiment of the present invention has the same beneficial effects as the negative electrode material provided in the second embodiment of the present invention, and will not be described in detail here.

[0097] The fourth embodiment of the present invention provides a lithium battery, including a negative electrode, an electrolyte, a positive electrode, a separator, and a shell for accommodating the negative electrode, the electrolyte, the positive electrode, and the separator, as provided in the third embodiment of the present invention. The separator is located between the negative electrode and the positive electrode, and the electrolyte is filled inside the shell.

[0098] It is understood that the lithium battery provided in the fourth embodiment of the present invention has the same beneficial effects as the negative electrode sheet provided in the third embodiment of the present invention, and will not be described in detail here.

[0099] It is understood that, in this embodiment of the invention, all first-principles calculations based on density functional theory (DFT) were performed using the Vienna Ab-initio Simulation Package (VASP). When dealing with electron exchange and correlation interactions, we selected the Perdew-Burke-Ernzerhof (PBE) functional within the framework of the Generalized Gradient Approximation (GGA). The basis set uses a plane wave cutoff energy of 450 eV, and the chemical composition strictly adheres to the actual synthesis conditions, perfectly matching the results of inductively coupled plasma (ICP) analysis. Spin polarization effects are introduced by setting the spin polarization parameter ISPIN = 2. A vacuum spacing of 20 Å is specifically set to eliminate interactions between periodic images. The structural relaxation process continues until the total energy converges to 1 × 10⁻⁶. -5 Below eV, atomic forces converge to below 0.03 eV / A.

[0100] Phase composition analysis of the materials was performed using a Bruker D8 Advance X-ray diffractometer (using copper Kα radiation), including in-situ analysis. The morphology, particle size, and elemental distribution of the samples were characterized using field emission scanning electron microscopy (FE-SEM, Thermo Fisher Scientific Apreo 2 S Lovac). Microstructural features such as lattice fringes and elemental distribution maps were observed using transmission electron microscopy (TEM, Thermo Fisher Scientific FEI Talos F200X), which also allows for real-time monitoring of structural evolution during phase transitions. The surface chemical states of HEO and PHEO materials were analyzed using a Thermo Fisher Scientific Escalab Xi+ X-ray photoelectron spectroscopy system. Raman spectroscopy was performed using a Renishaw inVia Qontor spectrometer (532 nm laser source) to obtain molecular structure information. The elemental composition of the samples was determined using a PerkinElmer 8300 inductively coupled plasma (ICP) analyzer. Thermal behavior and stability tests were performed using equipment from the Netzsch Group.

[0101] The foregoing has provided a detailed description of a method for preparing a negative electrode material, the negative electrode material, the negative electrode sheet, and the lithium battery disclosed in the embodiments of the present invention. Specific examples have been used to illustrate the principles and implementation methods of the present invention. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of the present invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention. Any modifications, equivalent substitutions, and improvements made within the principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a negative electrode material, characterized in that: Includes the following steps: A salt solution with a concentration of 0.1–1 mol / L is formed by mixing lithium salt with at least five metal salts. Add phosphate to the salt solution and stir for 30-50 minutes, then add a complexing agent and continue stirring to obtain a mixed solution; the phosphate includes one or more of ammonium dihydrogen phosphate, ammonium polyphosphate, and potassium dihydrogen phosphate; Continue stirring the mixture at 20–80°C until a gel forms; and The negative electrode material is obtained by drying, grinding, calcining, and grinding the gel, specifically including the following steps: The gel is dried at 100-150°C until completely dry, and then ground into powder. The ground powder is calcined at 600-800℃ for 1-3 hours to obtain calcined powder; The negative electrode material is obtained by grinding the calcined powder. The metal salt includes at least five of the following: chromium salt, manganese salt, iron salt, cobalt salt, nickel salt, zinc salt, copper salt, and magnesium salt; the lithium salt is LiNO3; the metal salt is a metal nitrate; and the complexing agent includes one or a combination of several of the following: anhydrous citric acid, tartaric acid, ethylenediaminetetraacetic acid, and oxalic acid. The nominal phosphorus doping concentration in the negative electrode material is 1% to 30%.

2. A negative electrode material, characterized in that: The negative electrode material is prepared by the method described in claim 1. The negative electrode material includes PO bonds of phosphate and POM bonds formed by the coordination bond between phosphate and the metal ion of the metal salt, where M represents the metal ion.

3. The negative electrode material as described in claim 2, characterized in that: The chemical formula of the negative electrode material is [P x (LiCrMnFeCoZn) 1-x ]3O4, where 0.02≤X≤0.

3.

4. The negative electrode material as described in claim 3, characterized in that: The negative electrode material is in particulate form with a particle size of 50–200 nm.

5. The negative electrode material as described in claim 2, characterized in that: When the nominal phosphorus doping concentration of the negative electrode material is 20%, the lattice parameters a=b=c=8.247279Å and V=560.96Å. 3 .

6. A negative electrode sheet, characterized in that: It includes a current collector and a negative electrode material as described in claim 2 disposed on at least one surface of the current collector.

7. A lithium battery, characterized in that: The device includes, as described in claim 6, a negative electrode, an electrolyte, a positive electrode, a separator, and a housing that contains the negative electrode, the electrolyte, the positive electrode, and the separator, wherein the separator is located between the negative electrode and the positive electrode, and the electrolyte is filled within the housing.

Citation Information

Patent Citations

  • Anode material of lithium ion battery and preparation method thereof

    CN102437323A

  • Preparation method and application of positive electrode material lithium iron phosphate

    CN112864384A